Dental anxiety: a comparison of students of dentistry, biology, and psychology - Storjord,Helene Persen; Teodorsen,Mari Mjønes; Bergdahl,Jan; Wynn,Rolf; Johnsen,Jan-Are Kolset (Journal of Multidisciplinary Healthcare, 2014)
Helene Persen Storjord,1 Mari Mjønes Teodorsen,1 Jan Bergdahl,1 Rolf Wynn,2,3 Jan-Are Kolset Johnsen1 1Department of Clinical Dentistry, 2Department of Clinical Medicine, UiT - The Arctic University of Norway, 3Division of Addictions and Specialized Psychiatric Services, University Hospital of North Norway, Tromsø, Norway Introduction: Dental anxiety is an important challenge for many patients and clinicians. It is thus of importance to know more about dental students' own experiences with dental anxiety and their understanding of dental anxiety. The aim was to investigate differences in dental anxiety levels between dental students, psychology students, and biology students at a Norwegian university. Materials and methods: A total of 510 students of dentistry, psychology, and biology at the University of Tromsø received a questionnaire consisting of the Modified Dental Anxiety Scale, demographic questions, and questions relating to their last visit to the dentist/dental hygienist; 169 students gave complete responses. Nonparametric tests were used to investigate differences between the student groups. Results: The respondents were 78% female and 22% male; their mean age was 24 years. The dental students showed a significantly lower degree of dental anxiety than the psychology (P<0.001) and biology students (P<0.001). A significant decrease in dental anxiety levels was found between novice and experienced dentistry students (P<0.001). Discussion: The dental students had less dental anxiety compared to psychology students and biology students. Experienced dental students also had less dental anxiety than novice dental students. This could indicate that the dentistry program structure at the university may influence dental anxiety levels. Conclusion: Dental anxiety seemed to be less frequent in dentistry students compared to students of biology or clinical psychology. The practice-oriented dentistry education at the university might contribute to the differences in anxiety levels between new and ...